Comparison of the effect of melatonin, dexmedetomidine, and gabapentin on reduction of postoperative pain and anxiety following laminectomy: a randomized clinical trial - Reza Jouybar; Somayeh Kazemifar; Naeimehossadat Asmarian; Ali Karami; Saeed Khademi (BMC Anesthesiology, 2022)
Abstract Background This study aimed to compare the effects of melatonin, dexmedetomidine, and gabapentin on postoperative pain and anxiety following laminectomy. Methods In this randomized clinical trial, 99 patients aged 40–60 years old with American Society of Anesthesiologists physical status I-II undergoing laminectomy were divided into three groups receiving 600mg gabapentin (group G), 10mg melatonin (group M), or starch tablets (group D). The Hospital Anxiety and Depression Scale (HADS) was used to measure postoperative anxiety while a Visual Analogue Scale (VAS) was employed to measure pain severity. Patients’ satisfaction with pain treatment was also measured together with the frequency of nausea and vomiting. Results The postoperative HADS decreased in all groups over time. Time and group had no significant interaction effect on the HADS score. Patients in the melatonin group had lower HADS at 2 and 6h after surgery. According to the VAS, the groups significantly differed in pain scores 6 and 24h after surgery. Lower VAS scores were observed 6h after surgery in the dexmedetomidine group compared with the gabapentin group and 24h after surgery in the dexmedetomidine group compared with the gabapentin and melatonin groups. Narcotic requirements, patients’ satisfaction, and vital sign changes did not significantly vary among the groups. Notably, patients in the melatonin group had less nausea and vomiting. Trial registration: This study was registered in the Iranian Registry of Clinical Trials (No. IRCT20141009019470N82, 29.06.2019) where the trial protocol could be accessed. Conclusion Melatonin is effective as a postoperative anti-anxiety drug. Dexmedetomidine is useful in reducing postoperative pain.